SOCIAL CAPITAL AND INTERNATIONALIZATION OF FAMILY SMEs IN CAMPECHE, MEXICO: A QUALITATIVE COMPARATIVE ANALYSIS - Cámara, Selina Salazar; Martín, David; González, Francisco Acedo (Review of Business Management, 2021)
Theoretical framework – Our review examines the relational approach to internationalization and the strategic approach to family businesses. It covers three types of social capital, market orientation, and international business orientation. Design/methodology/approach – This is a fuzzy-set qualitative case study. Seven family SMEs from the fishing sector in Campeche, Mexico, compose the sample. Findings – Linking is determining factor for internationalization. The cessation of internationalization occurs in family businesses because of a lack of international entrepreneurship, the family's presence, and a lack of vertical links. Practical & social implications – This study expands the research on internationalization in family SMEs in an emerging economy context, empirically demonstrating how the analyzed exporters' social capital links directly influence their activity. For business professionals, the challenge is to manage their links abroad. Our results show that links play a crucial role in internationalization in this context. Exporters that have not internationalized are advised to strengthen their connections with key government institutions. Originality/value – We show that there is more than one optimal way for family SMEs to succeed in internationalization. Research on the internationalization of family businesses in Mexico is very scarce. Thus, this study responds to calls for further research on the internationalization of SMEs in emerging economies.